Atypical Presentation of Novel Coronavirus Disease 2019 in a Peritoneal Dialysis Patient - Subhasish Bose MD, FASN; Sreedhar Adapa MD, FASN; Venu Madhav Konala MD, FACP; Hemapriya Gopalreddy MD; Salim Sohail MD, FASN; Srikanth Naramala MD, FACR; Hema Kondakindi MD; Vijayadershan Muppidi MBBS, FACP; Manoj V. Ramachandran MD; Peter J. Juran MD; Narothama Reddy Aeddula MD, FASN (SAGE Publishing, 2020)
Coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), is a rapidly spreading disease causing increased morbidity and mortality across the globe. There is limited available knowledge regarding the natural history of the SARS-CoV-2 infection. Other factors that are also making this infection spread like a pandemic include global travelers, lack of proven treatment, asymptomatic carriers, potential reinfection, underprepared global health care systems, and lack of public awareness and efforts to prevent further spread. It is understood that certain preexisting medical conditions increase the risk of mortality with COVID-19; however, the outcome of this disease in traditionally vulnerable chronic illnesses such as end-stage renal disease is not well documented. We present a case of a 56-year-old African American lady with end-stage renal disease on the peritoneal dialysis who presented predominantly with nausea, vomiting, and subsequently found to have COVID-19. We use this case to illustrate an atypical presentation of the COVID-19 in a vulnerable patient and discuss the literature.